2013
DOI: 10.1371/journal.ppat.1003166
|View full text |Cite
|
Sign up to set email alerts
|

Nox2 Modification of LDL Is Essential for Optimal Apolipoprotein B-mediated Control of agr Type III Staphylococcus aureus Quorum-sensing

Abstract: Staphylococcus aureus contains an autoinducing quorum-sensing system encoded within the agr operon that coordinates expression of virulence genes required for invasive infection. Allelic variation within agr has generated four agr specific groups, agr I–IV, each of which secretes a distinct autoinducing peptide pheromone (AIP1-4) that drives agr signaling. Because agr signaling mediates a phenotypic change in this pathogen from an adherent colonizing phenotype to one associated with considerable tissue injury … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
58
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 44 publications
(66 citation statements)
references
References 102 publications
(110 reference statements)
8
58
0
Order By: Relevance
“…We chose to focus on the disruption of agr QS as an antivirulence approach to S. aureus SSTIs due to their predominance in S. aureus disease manifestations, as well as the established contribution of agr in facilitating these infections (11)(12)(13)(14)19). For example, agr deletion mutants (⌬agr) are less pathogenic and more readily cleared during SSTIs than are wild-type strains (14,19), and host innate effectors that disrupt agr signaling limit disease in skin infection models (20)(21)(22). Importantly, the sterile supernatant from agr ϩ but not from agr-null S. aureus strains is sufficient to cause skin lesions similar to those in an active infection, definitively demonstrating the role of agr-regulated secreted virulence factors in skin pathogenesis (58).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We chose to focus on the disruption of agr QS as an antivirulence approach to S. aureus SSTIs due to their predominance in S. aureus disease manifestations, as well as the established contribution of agr in facilitating these infections (11)(12)(13)(14)19). For example, agr deletion mutants (⌬agr) are less pathogenic and more readily cleared during SSTIs than are wild-type strains (14,19), and host innate effectors that disrupt agr signaling limit disease in skin infection models (20)(21)(22). Importantly, the sterile supernatant from agr ϩ but not from agr-null S. aureus strains is sufficient to cause skin lesions similar to those in an active infection, definitively demonstrating the role of agr-regulated secreted virulence factors in skin pathogenesis (58).…”
Section: Discussionmentioning
confidence: 99%
“…S. aureus isolates have one of four agr alleles (agr-I to agr-IV), each encoding factors that secrete a unique AIP (AIP1 to AIP4, respectively) that is detected by a cognate AgrC histidine kinase; isolates from each allele can cause human disease (17,18). Importantly, we and others have shown that the disruption of agr signaling by mutagenesis, monoclonal antibodies, or host factors limits S. aureus infection and reduces pathogenesis (14,(19)(20)(21)(22)(23)(24), demonstrating that agr QS is a robust target for combating invasive S. aureus infection.…”
mentioning
confidence: 99%
“…AIP-mediated activation of AgrC can be inhibited with peptide analogs and small molecules, which diminishes S. aureus colonization and invasion of skin and soft tissues (43,46). AIP is inactivated by neutrophil Nox2 NADPH oxidase modification and apolipoprotein B binding (47,48), which interferes with agr-mediated quorum sensing when S. aureus enters the bloodstream (49,50). In agreement with this model, AgrC inhibitors do not affect staphylococcal load, abscess formation, or disease outcome when mice are challenged by i.v.…”
Section: Discussionmentioning
confidence: 99%
“…The details of this mechanism have been unveiled through a series of studies (30,31,37). Initially, it was observed that pooled human serum, but not lipoproteindeficient serum, could inhibit quorum sensing by an agr type I reporter strain during in vitro growth (31).…”
Section: Direct Action Of Serum and Ros On Agr Componentsmentioning
confidence: 99%